2003
DOI: 10.1067/mcp.2003.27
|View full text |Cite
|
Sign up to set email alerts
|

P‐glycoprotein‐mediated intestinal and biliary digoxin transport in humans

Abstract: Using segmental intestinal perfusion, we provide direct evidence that intestinal P-glycoprotein mediates substantial drug elimination after intravenous administration from the systemic circulation into the gut lumen and prevents entry of luminally administered P-glycoprotein substrates into the enterocytes. These data also highlight the relative importance of direct intestinal drug secretion in comparison with drug elimination through bile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 20 publications
7
130
0
2
Order By: Relevance
“…The impact of Pgp on oral bioavail-ability, intestinal excretion, and tissue distribution has been shown in mdr1a knockout mice (Schinkel et al, 1997a;Sparreboom et al, 1997). In humans, Pgp inhibition caused a significant decrease in digoxin intestinal excretion (Drescher et al, 2003), whereas rifampinup-regulated intestinal Pgp expression appeared to be responsible for a decrease in digoxin oral bioavailability (Greiner et al, 1999).…”
Section: Saquinavir [Sqv (N-tert-butyl-decahydro-2-[2(r)-hydroxy-4-pmentioning
confidence: 99%
“…The impact of Pgp on oral bioavail-ability, intestinal excretion, and tissue distribution has been shown in mdr1a knockout mice (Schinkel et al, 1997a;Sparreboom et al, 1997). In humans, Pgp inhibition caused a significant decrease in digoxin intestinal excretion (Drescher et al, 2003), whereas rifampinup-regulated intestinal Pgp expression appeared to be responsible for a decrease in digoxin oral bioavailability (Greiner et al, 1999).…”
Section: Saquinavir [Sqv (N-tert-butyl-decahydro-2-[2(r)-hydroxy-4-pmentioning
confidence: 99%
“…Inhibition of the P-gp transporter may also be the basis for drug-drug interactions. The classic example is the increase in oral bioavailability of digoxin when coadministered with the P-gp inhibitor quinidine (Drescher et al, 2003;Igel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Demeule et al [38] found that dexamethasone, which is a P-gp inducer, increased P-gp expression in the liver and the lung but reduced the expression of this molecule in the kidney. Transmembrane proteins in each tissue respond differently to inducers, as stated by Drescher et al [39] . AFB 1 is activated via the conversion into AFB 1 8-9 epoxide by cytochrome 450 enzymes, especially CYP1A2 and CYP3A4, and glutathione S-transferases are the most important enzymes for detoxifying AFB 1 in all species, including mice [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%